Neighborhood effects in hybrid rice adoption in Davao del Sur, Philippines - Miguel, Charisse B.; Sarmiento, Jon Marx P.; Estaña, Leo Manuel B.; Limpoco, Marie Analiz April A.; Calag, Vicente B.; Novero, Annabelle U.; Alviola, Pedro A. IV (2021)
"The Philippines adopted the hybrid rice technology in 1998 to increase productivity; however, the adoption rate is 9% of the total rice area in 2016. Thus, it is important to understand the adoption decisions of farmers in relation to hybrid rice technology. Previous studies of rice technology adoption in the Philippines did not consider the spatial dependencies, wherein the choice of adoption of a farmer is influenced by choice of the neighboring farmers" - title page.
Includes bibliographical references.
Keywords: Hybrid rice -- Philippines -- Davao del Sur